UPPER KASHKADARYA EMBROIDERY TERMINOLOGY: A STRUCTURAL AND SYNTACTIC OVERVIEW - Bahodirova Gulruh Bahodirovna (Web of Journals Publishing, 2025)
This article is devoted to the structural-morphological and syntactic features of embroidery terms. He analyzed embroidery terms lexically-morphologically into noun terms, adjective terms, and verb (name of action) terms. Instead, the meeting of these terms in folklore and artistic works was discussed.
Keywords: Embroidery, term, phrase, syntactic term, noun terms, adjective terms, verb terms.